2022
DOI: 10.3389/fphar.2022.939573
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Efficacy and Safety of Molnupiravir Against Omicron Variant Infection: A Randomized Controlled Clinical Trial

Abstract: Background: The rapid worldwide spread of the Omicron variant of SARS-CoV-2 has unleashed a new wave of COVID-19 outbreaks. The efficacy of molnupiravir, an approved drug, is still unknown in patients infected with the Omicron variant.Objective: Evaluated the antiviral efficacy and safety of molnupiravir in patients infected with SARS-CoV-2 Omicron variant, with symptom duration within 5 days.Methods: We conducted a randomized, controlled trial involving patients with mild or moderate COVID-19. Patients were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
54
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 11 publications
0
54
0
3
Order By: Relevance
“…This finding is consistent with the faster viral RNA clearance identified with molnupiravir use in the latest clinical trial conducted in hospitalised patients with mild-to-moderate COVID-19 of the omicron variant. 42 …”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with the faster viral RNA clearance identified with molnupiravir use in the latest clinical trial conducted in hospitalised patients with mild-to-moderate COVID-19 of the omicron variant. 42 …”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with faster viral RNA clearance identified with molnupiravir use in the latest clinical trial conducted among hospitalized patients with mild-to-moderate COVID-19 of the Omicron variant. 42 Meanwhile, results of our subgroup analyses seemed to suggest a lack of significant benefits in younger patients and those who had been fully vaccinated, which would add support to prioritize the prescription of oral antivirals to the elderly and those with inadequate vaccination, who were also likely at a higher risk of progression to severe COVID-19. Likewise, recent studies of nirmatrelvir/ritonavir during an Omicron surge have suggested significant clinical and mortality benefits in the elderly, yet insufficient evidence for younger patients.…”
Section: Discussionmentioning
confidence: 76%
“…In summary, it was found that the risk of hospitalization or death in high-risk unvaccinated adults with confirmed COVID-19 was significantly lower when treated early with molnupiravir. In a study conducted by Zou et al, (2022) 147 patients with COVID-19 were randomized to receive molnupiravir (n=80) and control (n=36). Following exclusions, 77 of them received 800mg molnupiravir twice daily for 5 days and 31 were in the control group (Zou et al, 2022).…”
Section: Molnupiravirmentioning
confidence: 99%
“…In a study conducted by Zou et al, (2022) 147 patients with COVID-19 were randomized to receive molnupiravir (n=80) and control (n=36). Following exclusions, 77 of them received 800mg molnupiravir twice daily for 5 days and 31 were in the control group (Zou et al, 2022). Treatment with molnupiravir was found to significantly reduce the viral load in collected pharyngeal swabs.…”
Section: Molnupiravirmentioning
confidence: 99%
See 1 more Smart Citation